Motivasi dan Perkembangan Denyut Nadi Remaja dalam Aktivitas Pendaki Gunung Lorokan pada Ranah Sport Recreation - Rochmatul Anjani; Catur Supriyanto; Andun Sudijandoko; Anindya Mar'atus Sholikhah (Mutiara Pendidikan dan Olahraga, 2025)
Recently, many teenagers have been doing mountain climbing, one of which is Mount Lorokan. This study examines the motivation of teenagers in climbing Mount Lorokan and looking for differences in heart rate before and after climbing. This study uses a quantitative descriptive type with a purposive sampling technique and a sample size of 30 respondents. The respondents' heart rate data was taken before and after climbing and then given a questionnaire consisting of 29 questions. It is known that the results of the pretest and posttest heart rate obtained a significant figure of 0.00 <0.05, which means that there is a difference in the heart rate of teenagers. Furthermore, the results of the motivation questionnaire show that the motivation of teenagers to climb Mount Lorokan is more influenced by intrinsic factors with a percentage value of 83.44%, compared to extrinsic factors which obtained a percentage value of 66.67%. Where each indicator has a percentage value, such as the indicator of the desire to explore one's abilities with an average value of 79.33% in the high category, the indicator of enjoying the beauty of nature with an average value of 86.33% in the very high category, the indicator of the need for relaxation with an average value of 84.67% in the very high category, the indicator of social pressure with an average value of 76.67% in the high category, the indicator of social media trends with an average value of 68.33% in the high category, and the indicator of recognition from others with an average value of 55% in the sufficient category.